Reka Devnia (Bulgaria): the challenges of creating a digital dataset of 80,000 coins - Spoerri Butcher, M (EUT Edizioni Università di Trieste, 2019)
The hoard of Reka Devnia (Bulgaria) was found in 1929 on the site of ancient Marcianopolis. It comprised more than a 100,000 coins, mainly denarii, with some antoniniani and a minority of provincial silver. Issues range from Republican denarii of Mark Antony (32/31 BC) to antoniniani of Trajan Decius (AD 251). 81,096 coins were transferred to two Bulgarian museums and subsequently published by the Bulgarian numismatist N. A. Mouchmov. A digital dataset, based on the publication of Mouchmov, has now been made available within the Coin Hoards of the Roman Empire project (http://chre.ashmus.ox.ac.uk/hoard/3406). It gives details of entries at type level, providing references to Cohen, used in the original publication, updated RIC references, and web links to online portals presenting standard typologies of republican, imperial or provincial coinages. This paper will look at the challenges of such an enterprise, from providing updated references for coin types solely known from the brief descriptions given by Mouchmov, to providing links to online portals such as OCRE.